Master tracks in different resolutions of ALKOR cruise AL632, Kiel - Kiel, 2025-05-07 - 2025-05-19 - Thorsten B H Reusch; Felix H Mittermayer (PANGAEA, 2025)
Raw data acquired by position sensors on board RV Alkor during expedition AL632 were processed to receive a validated master track which can be used as reference of further expedition data. During AL632 data from the Seapath 330 system, the Furuno GP-170 and the Furuno GP-150 GPS receivers were used to calculate the mastertrack. Data were downloaded from DAVIS SHIP data base (http://dship.bsh.de) with a resolution of 1 sec. Processing and evaluation of the data is outlined in the data processing report. Processed data are provided as a master track with 1 sec resolution derived from the position sensors extquotesingle data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.